A comparative investigation on the effect of different nanofluids on the thermal performance of two-phase closed thermosyphon. (March 2020) - Xu, Qian; Liu, Lin; Feng, Junxiao; Qiao, Lihong; Yu, Chuqiao; Shi, Wenjun; Ding, Chong; Zang, Yong; Chang, Chun; Xiong, Yaxuan; Ding, Yulong
Highlights: l The performance of the TPCT using different nanofluids are studied experimentally. l The effects of various operating conditions on thermal performance are studied. l The results manifest that the hybrid nanofluid intensified the heat transfer. l Thermal efficiency of hybrid nanofluid increased by 10.6%, compared with the DW. Abstract: The heat transfer performance of single and hybrid nanofluids in a two-phase closed thermosyphon (TPCT) was experimentally studied and compared with deionized water (DW). Al2 O3 and TiO2 nanoparticles with a volume concentration of 0.2% were added to the DW in two steps to prepare stable nanofluid suspensions (Al2 O3 H2O, TiO2 H2 O, 75% Al2 O3  + 25% TiO2 H2 O, 50% Al2 O3  + 50% TiO2 H2 O, and 25% Al2 O3  + 75% TiO2 H2 O). The TPCT was made of a carbon steel tube of length 500 mm, outer diameter 20 mm, and wall thickness 2 mm. In this study, through an orthogonal experiment, the five types of nanofluids were analyzed to obtain the single and hybrid nanofluids with the best heat transfer performance. These were compared with DW under various conditions of the heating power, which were varied from 200 to 400 W in equal steps of 50 W, the liquid filling ratio (30%, 50%, 70%), and the cooling water flow rate (0.4, 0.48, 0.56 L/min). The results showed that when the hybrid nanofluid 25% Al2 O3  + 75% TiO2 H2 O and the single nanofluid TiO2 H2 O were used instead of DW, the best heat transfer performance was displayed. For the heating input of 400 W, filling ratio of 50%, and cooling water flow of 0.4 L/min, the thermal resistance of the TPCT was reduced by 26.8% and 22.8%, the equivalent heat transfer coefficient increased by 25.78% and 21.62%, the thermal efficiency was increased by 10.6% and 9.2%, respectively.